Impact of grain coats on quartz overgrowth and Reservoir properties - Busch, Benjamin (KIT Scientific Publishing, 2017)
Syntaxial overgrowth cementation, and thereby reservoir quality, can be affected by grain coating phases inhibiting nucleation. Reaction kinetics provide a means to model the development of cement phases over time. Additional algorithms constraining compaction behavior, porosity, and permeability development are used to model reservoir quality. Sub-vertical deformation bands can compartmentalize reservoirs by impacting bed-parallel permeability and preserve geochemical alterations.